2015
DOI: 10.1007/s13197-015-1934-9
|View full text |Cite
|
Sign up to set email alerts
|

Bread enriched in lycopene and other bioactive compounds by addition of dry tomato waste

Abstract: The tomato processing industry generates high amounts of waste, mainly tomato skins and seeds, which create environmental problems. These residues are attractive sources of valuable bioactive components and pigments. A relatively simple recovery technology could consist of production of powders to be directly incorporated into foods. Tomato waste coming from a Romanian tomato processing unit were analyzed for the content of several bioactive compounds like ascorbic acid, β-carotene, lycopene, total phenolics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 39 publications
(51 reference statements)
9
68
1
1
Order By: Relevance
“…The tomato seeds were separated and cleaned after our own developed procedure from the tomato by-product (peel, pulp and seeds) with water, at the temperature of 24 • C, after which they were dried in a tray dryer (Memmert UF30, City, Schwabach, Germany) at 50 • C until its moisture content reached less than 10% (wet basis). This was to limit the loss of available bioactive compounds which are still available even at high levels of drying temperature, namely 60 • C according to Nour et al [15] or 70 • C according to Sogi et al [22]. After cooling, the tomato seed were ground in an electrical mill (Heinner, Navy 150, Guangdong City, China).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tomato seeds were separated and cleaned after our own developed procedure from the tomato by-product (peel, pulp and seeds) with water, at the temperature of 24 • C, after which they were dried in a tray dryer (Memmert UF30, City, Schwabach, Germany) at 50 • C until its moisture content reached less than 10% (wet basis). This was to limit the loss of available bioactive compounds which are still available even at high levels of drying temperature, namely 60 • C according to Nour et al [15] or 70 • C according to Sogi et al [22]. After cooling, the tomato seed were ground in an electrical mill (Heinner, Navy 150, Guangdong City, China).…”
Section: Introductionmentioning
confidence: 99%
“…In the chemical composition of tomato pomace high level of total dietary fibers, proteins, fats and medium amounts of ash are found [14].The peel and seed by-products of tomato pomace represents approximately 20-50 g·kg −1 of the initial weight of tomatoes and can be used individually or combined [14]. Regarding the combined utilization, the literature reports that, due to the significant amounts of bioactive phytochemicals from tomato pomace, it can be used as natural antioxidants for the formulation of functional foods, or as additives in food systems to extend their shelf-life [15][16][17]. Other studies showed that tomato pomace can be considered a good source of some macroelements, such as potassium, manganese and calcium and microelements, i.e., copper and zinc, which are cofactors of the antioxidant enzymes [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Iceberg lettuce flour could thus be exploited to increase white bread phenolic content, being rich in these compounds (Llorach et al ., ; Naczk & Shahidi, ). An increase in phenolic content and antioxidant activity of bakery products was also obtained by adding mango peel, dried tomato waste, broccoli, carrot and beetroot (Ajila et al ., ; Nour et al ., ; Ranawana et al ., ). By contrast, no change in total phenolic was detected when apple and lemon fibre was added to cookies (Bilgiçli et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…This goal could be equally reached using flours from fruit and vegetables or from their wastes, which are often richer in nutritional compounds (Nilnakara et al, 2009;Mastromatteo et al, 2012). Functional bread has been produced using flours from tomato, cabbage and pineapple waste (Nilnakara et al, 2009;Nour et al, 2015;Wu & Shiau, 2015;Chareonthaikij et al, 2016).…”
Section: Introductionmentioning
confidence: 99%